2022
DOI: 10.1177/14777606221145702
|View full text |Cite
|
Sign up to set email alerts
|

Design of experiments to compare the reprocessing effect with Fused Deposition Modeling printing parameters on mechanical properties of Polylactic Acid specimens towards circular economy

Abstract: Distributed Recycling via Additive Manufacturing (DRAM) is a closed-loop material reprocessing solution that promotes circular economy. There are several literature gaps related to material properties and recycling cycles at different stages of the DRAM process. With an approach to filling these gaps, a small contribution has been made through this work by comparing the effect of reprocessing cycles (recycling) with the effect of FDM printing parameters such as Raster angle orientation, Infill density and Extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…As the average molecular weight decreases, the rheological behaviour changes [151], and the printability worsens with it [152]. When FFF parts are crushed and recycled for printing again, the mechanical strength of the printed parts can be retained over a few re-processing cycles, typically 1 or 2, but is then expected to drop [135,[153][154][155][156][157]. In an experimental study that investigated the potential of close-looped recycling of PLA, commercial granules were extruded and printed.…”
Section: Thermoplastic Matrixmentioning
confidence: 99%
“…As the average molecular weight decreases, the rheological behaviour changes [151], and the printability worsens with it [152]. When FFF parts are crushed and recycled for printing again, the mechanical strength of the printed parts can be retained over a few re-processing cycles, typically 1 or 2, but is then expected to drop [135,[153][154][155][156][157]. In an experimental study that investigated the potential of close-looped recycling of PLA, commercial granules were extruded and printed.…”
Section: Thermoplastic Matrixmentioning
confidence: 99%
“…For 3D-printed parts, improving mechanical properties is a topic that has acquired great importance in recent years [ 7 , 8 ]. Several research papers have studied the correlation between printing parameters and mechanical properties, such as the ultimate tensile strength (UTS) [ 9 , 10 , 11 ], even after recycling cycles [ 12 ] or changes in the color of the filament [ 13 ]. The results of these studies have demonstrated the non-linearity of the process and the complex interaction between parameters; in most cases, this results in parts with anisotropic mechanical properties [ 11 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%